Analisis Kegagalan Berpikir Kritis Siswa Berdasarkan Self-Efficacy pada Materi SPLDV - Endika, Dwi Intan; Huda, Nizlel; Marzal, Jefri (Media Pendidikan Matematika, 2025)
This study aims to analyze the forms of students’ critical thinking failures in solving problems on the topic of Systems of Linear Equations in Two Variables (SPLDV) based on their levels of self-efficacy. This research employed a descriptive qualitative approach involving three eighth-grade students from SMPN 15 Muaro Jambi, selected through purposive sampling to represent high, medium, and low levels of self-efficacy. Data were collected through a critical thinking test based on the FRISCO indicators, in-depth interviews, observation of students’ cognitive processes, and documentation of their problem-solving steps. The findings indicate that students’ critical thinking abilities are still not optimal, particularly in the indicators of Reason, Inference, and Overview. Students with high self-efficacy demonstrated good understanding of the context and were able to construct mathematical models accurately, but they were still weak in interpreting results and reflecting on their solutions. Students with medium self-efficacy made algebraic reasoning errors and failed to evaluate the reasonableness of their answers. Meanwhile, students with low self-efficacy experienced difficulties across all stages, including understanding the context, selecting appropriate strategies, and evaluating their final solutions. These results reveal that differences in self-efficacy levels significantly influence the quality of students’ critical thinking processes. This study highlights the need to strengthen both cognitive and affective aspects to enhance students’ critical thinking skills in mathematics learning. Keywords: critical thinking, FRISCO, self-efficacy, SPLDV, mathematics education